Increasing Student Activeness Through Problem Based Learning at PKn Class IV SDN Gili Timur 2 - Siti Muhajiroh; Hanisah Rica Nurrahma; Tria Priska Amanti; Thiyaporn Kantathanawat (Journal of Action Research in Education, 2024)
This study aims to investigate the use of Problem-Based Learning (PBL) model in enhancing students’ learning activity. The research method employed is classroom action research (CAR) consisting of two cycles. The subjects of this research are 38 fourth-grade students of SDN Gili Timur 2 Elementary School. The results of this study indicate that the percentage of student learning activity increased from the first cycle to the second cycle. In the first cycle, the percentage of student activity was 60 percent, and in the second cycle, it further increased to 81 percent. The average results in the second cycle show that learning activity and the implementation of PBL are categorized as very good due to the improvement. The research findings demonstrate that PBL is effective in enhancing student activity in PKn learning. Thus, PBL can be considered as an effective alternative learning model to improve student learning activity. This research provides a significant contribution to improving the quality of education at SDN Gili Timur 2